2011
DOI: 10.1186/1532-429x-13-34
|View full text |Cite
|
Sign up to set email alerts
|

Effect of deferiprone or deferoxamine on right ventricular function in thalassemia major patients with myocardial iron overload

Abstract: BackgroundThalassaemia major (TM) patients need regular blood transfusions that lead to accumulation of iron and death from heart failure. Deferiprone has been reported to be superior to deferoxamine for the removal of cardiac iron and improvement in left ventricular (LV) function but little is known of their relative effects on the right ventricle (RV), which is being increasingly recognised as an important prognostic factor in cardiomyopathy. Therefore data from a prospective randomised controlled trial (RCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…Cardiac T2* improved after 1 year of treatment with DFO by 7-13% Pennell et al, 2014;Smith et al, 2011), and after 1 and 3 years of treatment with DFX by 12-29% (Merchant et al, 2012;Pennell et al, 2014) and 43% , respectively. DFO improved LVEF by only 0.3-2% (Maggio et al, 2002;Pennell et al, 2006), and DFX did not alter LVEF (Merchant et al, 2012;Pennell et al, 2014) after 1 year of treatment.…”
Section: Effects Of Dfo+dfxmentioning
confidence: 89%
“…Cardiac T2* improved after 1 year of treatment with DFO by 7-13% Pennell et al, 2014;Smith et al, 2011), and after 1 and 3 years of treatment with DFX by 12-29% (Merchant et al, 2012;Pennell et al, 2014) and 43% , respectively. DFO improved LVEF by only 0.3-2% (Maggio et al, 2002;Pennell et al, 2006), and DFX did not alter LVEF (Merchant et al, 2012;Pennell et al, 2014) after 1 year of treatment.…”
Section: Effects Of Dfo+dfxmentioning
confidence: 89%
“…Many studies have shown that DFO, DFP and DFX can cause a reduction in myocardial iron and improve cardiac function in b-thalassemia patients. 55,[60][61][62][63][64][65] However, it has been suggested that combined chelation therapy be used in some iron overload b-thalassemia patients who have shown no improvement when treated with a single iron chelator, due to its increased efficacy. [62][63][64][65] At this time, new evidence indicates a greater efficacy for iron chelation when an iron chelator was combined with an antioxidant such as vitamin E and N-acetylcysteine (NAC).…”
Section: Cardiac Complications In Beta-thalassemia Patientsmentioning
confidence: 99%
“…However, the price of this medication is unaffordable for most patients. Deferiprone (DFP), a cheaper oral iron chelator proven effective in achieving a negative iron balance in many short- and long-term clinical trials in adult patients with iron overload[3,4,5,6,7,8,9], has recently been studied for its efficacy and safety in thalassemia children receiving chelation [10,11,12,13,14,15,16,17]. To improve the efficacy of chelation treatment, the ‘iron shuttle hypothesis' [18,19] has been proposed, leading to many studies on the combined use of DFP and DFO [10,11,20,21,22,23,24,25,26,27,28,29,30].…”
Section: Introductionmentioning
confidence: 99%